2011
DOI: 10.1165/rcmb.2010-0347oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoplasmic Reticulum Stress in Epithelial–Mesenchymal Transition of Alveolar Epithelial Cells

Abstract: Endoplasmic reticulum (ER) stress has been implicated in alveolar epithelial type II (AT2) cell apoptosis in idiopathic pulmonary fibrosis. We hypothesized that ER stress (either chemically induced or due to accumulation of misfolded proteins) is also associated with epithelial-mesenchymal transition (EMT) in alveolar epithelial cells (AECs). ER stress inducers, thapsigargin (TG) or tunicamycin (TN), increased expression of ER chaperone, Grp78, and spliced X-box binding protein 1, decreased epithelial markers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
143
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 49 publications
13
143
0
1
Order By: Relevance
“…It is therefore worth noting that ER stress is a well-recognised inducer of EMT in the lung. Expression of mutant SFTPC, for example in primary murine AECII or AECII-like cell lines triggers morphological and biochemical EMT, and similar changes occur following treatment with chemical inducers of ER stress [17].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…It is therefore worth noting that ER stress is a well-recognised inducer of EMT in the lung. Expression of mutant SFTPC, for example in primary murine AECII or AECII-like cell lines triggers morphological and biochemical EMT, and similar changes occur following treatment with chemical inducers of ER stress [17].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…*Po0.05 vs HPMCs isolated from the omentum. 19 Apoptosis of HPMCs may also be induced by a CHOPindependent pathway via the activation of JNK, caspase, or mitochondrial cytochrome C. Interestingly, in contrast to the role of smad2/3 in EMT, smad2/3 activation was mediated by neither ER stress-nor TGF-β1-induced apoptosis in HPMCs in our study ( Supplementary Figures S4 and S6). Beneficial effect of preconditioning with ER stress was demonstrated in an animal model of mesangioproliferative glomerulonephritis.…”
Section: Discussionmentioning
confidence: 49%
“…20 The role of the UPR and ER stress has been demonstrated in idiopathic pulmonary fibrosis, as well as glomerulonephritis, diabetic nephropathy and drug-induced renal damage. 17,19,43,44 Despite ample evidence regarding the role of ER stress in organ fibrosis, the about ER stress and peritoneal fibrosis remain very limited. Previous studies revealed ultrastructural alterations of rough ER in the parietal peritoneum of patients on PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations